Black men's experiences of support following treatment for prostate cancer in England: A qualitative study. (February 2023) - Alexis, Obrey; Worsley, Aaron James
Abstract: Purpose: Prostate cancer is a leading cause of death in black men in the United Kingdom (UK). Evidence suggests that unmet supportive care needs are prevalent in contemporary healthcare, particularly for men with advanced prostate cancer, whilst less has been written specifically about the supportive care needs of black men. Therefore this study will examine black men's experiences of support following prostate cancer treatment in England. Method: A qualitative research design was employed. Twenty black African and black Caribbean men were interviewed on a face-to-face basis to obtain insightful information about their experiences of prostate cancer. Interviews were recorded and transcribed. Data were analysed using thematic analysis which allowed for emergent themes. Results: In this study there were six emergent themes. These were: dealing with the treatment effect, support from loved ones, individuals and organisations, healthcare support, spirituality, and positivity. Black men used different coping strategies to deal with the side effects of treatment. Conclusion: Black men experienced a range of supportive care needs. Some men felt that their individual needs as black men were not met by healthcare professionals, although no specific reasons were forthcoming as to why they felt this way. Healthcare professionals should be aware of the support mechanisms that black men have used throughout the prostate cancer journey and to consider these approaches when treating and caring for black men. Highlights: Black men in the UK found support through various means, such as being transferred to a support group, or self-supporting, such as relying on their spirituality. They cited support from their families and friends, support from organisations, and their faith as crucial elements to their wellbeing. Some men felt that their individual needs as black men were not met by UK healthcare professionals, although no specific reasons were forthcoming as to why they felt this way.